Inferences on location parameter in multivariate skew-normal family with unknown scale parameter. Issue 9 (27th September 2022) - Ma, Ziwei; Chen, Ying-Ju; Wang, Tonghui; Liu, Jing
Abstract: In this paper, the statistical inference on the location parameter vector is studied in the multivariate skew-normal model with unknown scale parameter and known shape parameter. Based on the distribution of the generalized Hotelling's T 2 statistic, confidence regions and hypothesis tests on the location parameter, μ, are obtained. The power function of the test is studied numerically as well. For illustration the effectiveness and applicability of our purposed methods, the traffic accident data from the National Highway Traffic Safety Administration (NHTSA) in U.S. Department of Transportation are analyzed.